Kecukupan Modal, Loan to Deposit Ratio, Pertumbuhan Nasabah dan Profitabilitas - Puspaningrum, Ni Luh Putu Andra; Diantini, Ni Nyoman Ayu (E-Jurnal Akuntansi, 2023)
The importance of the existence of LPDs in traditional villages requires LPDs to always maintain the stability of their profit growth, so it is important for LPDs to know the factors that influence their profitability. The research aims to analyze and determine the influence of capital adequacy, loan to deposit ratio and customer growth on LPD profitability in Denpasar City during the 2019-2021 period. The population in the study were all LPDs in Denpasar City with a total sample of 34 LPDs taken using the purposive sampling method. The research uses secondary data, namely financial reports obtained from LPLPD Denpasar City, and the data is analyzed using multiple linear regression analysis. The research results show that capital adequacy and customer growth have no effect on LPD profitability in Denpasar City, the loan to deposit ratio has a positive effect on LPD profitability in Denpasar City. Keywords: Capital Adequacy; Loan to Deposit Ratio; Customer Growth; Profitability